PEMUTAKHIRAN NILAI INDIKASI RATA-RATA DAN IMPLIKASINYA TERHADAP BESARAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (Studi Di Kabupaten Blitar) - Sudjatno Sudjatno (Universitas Muhammadiyah Malang, 2020)
Land as the object of Land and Property of Rural and Urban Tax (PBB-P2) has always changed in value from time to time. Considering the land value as the basis for the imposition of PBB-P2, the land value in a certain period needs to be updated, so the determination of the amount of PBB-P2 is in accordance with the actual land value. The purpose of this study is to determine the level of change of the Average Indication Value (NIR) before and after updating and to determine the effect of the updating NIR on the PBB-P2. This study uses a quantitative approach. The data used are primary and secondary data obtained through observation and documentation. The updating results show that the NIR and the Tax Object Sales Value (NJOP) in each Land Value Zone (ZNT) as a whole have increased, and the increase in NIR is higher than NJOP. Wilcoxon Signed Rank Test on NIR changes before and after updating show a significant increase before and after updating. The PBB-P2 determination based on land valuation with NIR results is greater than the land valuation method using NJOP. NIR is better to represent land value in accordance with prevailing market conditions